Epigenome‐wide association study of sarcopenia: findings from the Hertfordshire Sarcopenia Study (HSS). Issue 1 (4th December 2021) - Antoun, Elie; Garratt, Emma S.; Taddei, Andrea; Burton, Mark A.; Barton, Sheila J.; Titcombe, Phil; Westbury, Leo D.; Baczynska, Alicia; Migliavacca, Eugenia; Feige, Jerome N.; Sydall, Holly E.; Dennison, Elaine; et al.
Abstract: Background: Sarcopenia is the age‐related loss of muscle mass, strength, and function. Epigenetic processes such as DNA methylation, which integrate both genetic and environmental exposures, have been suggested to contribute to the development of sarcopenia. This study aimed to determine whether differences in the muscle methylome are associated with sarcopenia and its component measures: grip strength, appendicular lean mass index (ALMi), and gait speed. Methods: Using the Infinium Human MethylationEPIC BeadChip, we measured DNA methylation in vastus lateralis muscle biopsies of 83 male participants (12 with sarcopenia) with a mean (standard deviation) age of 75.7 (3.6) years from the Hertfordshire Sarcopenia Study (HSS) and Hertfordshire Sarcopenia Study extension (HSSe) and examined associations with sarcopenia and its components. Pathway, histone mark, and transcription factor enrichment of the differentially methylated CpGs (dmCpGs) were determined, and sodium bisulfite pyrosequencing was used to validate the sarcopenia‐associated dmCpGs. Human primary myoblasts ( n  = 6) isolated from vastus lateralis muscle biopsies from male individuals from HSSe were treated with the EZH2 inhibitor GSK343 to assess how perturbations in epigenetic processes may impact myoblast differentiation and fusion, measured by PAX7 and MYHC immunocytochemistry, and mitochondrial bioenergetics determined using the Seahorse XF96. Results: Sarcopenia was associated with differential methylation at 176 dmCpGs (false discovery rate ≤ 0.05) and 141 differentially methylated regions (Stouffer ≤ 0.05). The sarcopenia‐associated dmCpGs were enriched in genes associated with myotube fusion ( P  = 1.40E‐03), oxidative phosphorylation ( P  = 2.78E‐02), and voltage‐gated calcium channels ( P  = 1.59E‐04). ALMi was associated with 71 dmCpGs, grip strength with 49 dmCpGs, and gait speed with 23 dmCpGs (false discovery rate ≤ 0.05). There was significant overlap between the dmCpGs associated with sarcopenia and ALMi ( P  = 3.4E‐35), sarcopenia and gait speed ( P  = 4.78E‐03), and sarcopenia and grip strength ( P  = 7.55E‐06). There was also an over‐representation of the sarcopenia, ALMi, grip strength, and gait speed‐associated dmCpGs with sites of H3K27 trimethylation (all P  ≤ 0.05) and amongst EZH2 target genes (all P  ≤ 0.05). Furthermore, treatment of human primary myoblasts with the EZH2 inhibitor GSK343 inhibitor led to an increase in PAX7 expression ( P  ≤ 0.05), decreased myotube fusion ( P  = 0.043), and an increase in ATP production ( P  = 0.008), with alterations in the DNA methylation of genes involved in oxidative phosphorylation and myogenesis. Conclusions: These findings show that differences in the muscle methylome are associated with sarcopenia and individual measures of muscle mass, strength, and function in older individuals. This suggests that changes in the epigenetic regulation of genes may contribute to impaired muscle function in later life.